Extreme Events design and Mitigation Methods: A Review - Lawali Moussa Laminou; Zhangjun Liu; Xinghua Chen (Salehan Institute of Higher Education, 2019)
Recently, extreme events have highlighted their potentially tragic effects on structural and infrastructure systems. Resilience of the Community to these extreme vents is an important issue of increasing more concern for developing design methods. Such extreme events scenarios involve many uncertainties, such as the intensity, location, and period. The extreme events may include those caused by various natural or manmade hazards, such as earthquake, strong winds, fire, blast, etc. Compared to other events, earthquake and wind are particularly critical due to their significant threats to the global structure performance and more challenges for design. Researchers have recognized that proper evaluation, modeling, and assessment of the effects of extreme events are fundamental to ensure the desired performance of structures. Therefore, the concern for developing appropriate methodologies to evaluate and design structures that can withstand the effects of extreme events has become a very active field of research in recent years. Improvement of building codes and development of new strategies are needed to mitigate the disastrous effects of extreme events. This paper presents a comprehensive review of literature surrounding designing building structures for extreme events. First, a general overview of the extreme events design and different objectives of approaches is conducted. Furthermore, a review related literature surrounding designing for earthquake resistance guidelines is presented, also highlights Performance-Based Seismic Design objectives. The available literature includes many studies for the provisions included in different design codes (China, United States and Europe). A review of literature related to wind resistance design with an overview of Performance Based Wind Design of building design method for the control of winds impacting on building structures is also presented.